Methylation of CpG 5962 in L1 of the human papillomavirus 16 genome as a potential predictive marker for viral persistence: A prospective large cohort study using cervical swab samples. (19th December 2019) - Fertey, Jasmin; Hagmann, Jörg; Ruscheweyh, Hans‐Joachim; Munk, Christian; Kjaer, Susanne; Huson, Daniel; Haedicke‐Jarboui, Juliane; Stubenrauch, Frank; Iftner, Thomas
Abstract: Several studies have demonstrated that the viral genome can be methylated by the host cell during progression from persistent infection to cervical cancer. The aim of this study was to investigate whether methylation at a specific site could predict the development of viral persistence and whether viral load shows a correlation with specific methylation patterns. HPV16‐positive samples from women aged 20–29 years (n = 99) with a follow‐up time of 13 years, were included from a Danish cohort comprising 11 088 women. Viral load was measured by real‐time PCR and methylation status was determined for 39 CpG sites in the upstream regulatory region (URR), E6/E7, and L1 region of HPV16 by next‐generation sequencing. Participants were divided into two groups according to whether they were persistently (≥ 24 months) or transiently HPV16 infected. The general methylation status was significantly different between women with a persistent and women with a transient infection outcome ( P  = .025). One site located in L1 (nt. 5962) was statistically significantly ( P  = .00048) different in the methylation status after correction using the Holm‐Sidak method (alpha = 0.05). Correlation analyses of samples from HPV16 persistently infected women suggest that methylation is higher although viral load is lower. This study indicates that methylation at position 5962 of the HPV16 genome within the L1 gene might be a predictive marker for the development of a persistent HPV16 infection. Abstract : Persistent HPV16 infections are the main risk factor for the development of cancer of the cervix uteri. Currently, no biomarkers are available to determine the probability for a persistent HPV16 infection after a single HPV test. This study indicates that DNA methylation at position 5962 in the HPV16 L1 gene might be a predictive marker for a persistent HPV16 infection.